Modelling the distribution of fishing-related floating marine litter within the Bay of Biscay and its marine protected areas. (1st January 2022) - Ruiz, Irene; Ana J., Abascal; Basurko, Oihane C.; Rubio, Anna
Abstract: Sea-based sources account for 32–50 % of total marine litter found at the European basins with the fisheries sector comprising almost 65 % of litter releases. In the south-east coastal waters of the Bay of Biscay this figure approaches the contribution of just the floating marine litter fraction. This study seeks to enhance knowledge on the distribution patterns of floating marine litter generated by the fisheries sector within the Bay of Biscay and in particular on target priority Marine Protected Areas (MPAs) to reinforce marine litter prevention and mitigation policies. This objective is reached by combining the data on geographical distribution and intensity of fishing activity, long-term historical met-ocean databases, Monte Carlo simulations and Lagrangian modelling with floating marine litter source and abundance estimates for the Bay of Biscay. Results represent trajectories for two groups of fishing-related items considering their exposure to wind; they also provide their concentration within 34 MPAs. Zero windage coefficient is applied for low buoyant items not subjected to wind effect. Highly buoyant items, strongly driven by winds, are forced by currents and winds, using a windage coefficient of 4 %. Results show a high temporal variability on the distribution for both groups consistent with the met-ocean conditions in the area. Fishing-related items driven by a high windage coefficient rapidly beach, mainly in summer, and are almost non-existent on the sea surface after 90 days from releasing. This underlines the importance of windage effect on the coastal accumulation for the Bay of Biscay. Only around 20 % of particles escaped through the boundaries for both groups which gives added strength to the notion that the Bay of Biscay acts as accumulation region for marine litter. MPAs located over the French continental shelf experienced the highest concentrations (>75 particles/km 2 ) suggesting their vulnerability and need for additional protection measures. Graphical abstract: Image 1 Highlights: Fishing-related FML items are modelled considering their buoyancy. Highly buoyant items beach after 30 days, only 1 % remain floating after 90 days. Half of low buoyant items remain floating after 90 days and 20–35 % beach. Only 20 % of items escape the Bay of Biscay, mostly through the northern boundary. French MPAs are substantially affected by highly buoyant items.